An Analysis of Teacher’s Pedagogical Competence in Teaching English for Sixthgrade of SDTQ Muadz Bin Jabal Kendari - Nanzairinah, Asti; Suhartini, Lelly (Universitas Halu Oleo, 2021)
This research was conducted to find out how the teacher pedagogical competence in Teaching English at The Sixth Grade of SDTQ Muadz Bin Jabal Kendari. The researcher used descriptive analysis as the researcher design. The data source was collected from two teachers of class 6th. The researcher used the triangulation technique, namely interview, observation, and video recording in this study. The result shows that the teacher pedagogical competence still needs improvement such as their competence in using teaching method since they still used conventional method in this case is lecturing method. Related to teaching method, the teacher should be creative to carry out an activity to be organized. The teacher also did not provide feedback for the students. In term of the young learner, the teacher may use cooperative learning model to make their teaching more attractive. It was recommended to the teacher to use various teaching style or find another reference to create a better teaching model.